Studi Termokimia Kuantum untuk Derivatif Flavonoid: Perbandingan Stabilitas Energi dan Aktivitas Antiradikal berdasarkan Metodologi DFT/B3LYP - Ahmad Pratama; Lilis Kurniawati; Dwi Handayani (Lembaga Publikasi Ilmiah Nusantara, 2025)
Flavonoids are a class of natural phenolic compounds with broad biological activities, particularly as antioxidants. Understanding the mechanism and efficiency of the antiradical activity of flavonoids can be achieved through the density functional theory (DFT) approach, which enables the analysis of bond energies and molecular reactivity parameters. This study employed the DFT/B3LYP method with the 6-31G(d,p) basis set to evaluate the energy stability and antiradical activity of several flavonoid derivatives. The analysis focused on ionization energy, electron affinity, HOMO–LUMO energy, and hydrogen atom donation potential. The computational results indicated that hydroxyl group substitution at specific positions influences antiradical capacity through resonance stabilization and reduction of O–H bond energy. Derivatives bearing hydroxyl groups at the ortho and para positions tend to be more stable and possess higher antiradical potential compared to other substitutions. These findings reinforce the role of DFT as a predictive tool for understanding the structure–antioxidant activity relationship in flavonoids, which is valuable for the development of bioactive compounds in pharmaceutical and food applications.